2014
DOI: 10.1021/jm500290c
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble and Cleavable Quercetin–Amino Acid Conjugates as Safe Modulators for P-Glycoprotein-Based Multidrug Resistance

Abstract: Quercetin-amino acid conjugates with alanine or glutamic acid moiety attached at 7-O and/or 3-O position of quercetin were prepared, and their multidrug resistance (MDR)-modulatory effects were evaluated. A quercetin-glutamic acid conjugate, 7-O-Glu-Q (3a), was as potent as verapamil in reversing MDR and sensitized MDR MES-SA/Dx5 cells to various anticancer drugs with EC50 values of 0.8-0.9 μM. Analysis on Rh-123 accumulation confirmed that 3a inhibits drug efflux by Pgp, and Pgp ATPase assay showed that 3a in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 75 publications
0
46
0
2
Order By: Relevance
“…Thus, in the presence of reserpine (MEC, 4 μg/mL), the MIC of EtBr was reduced to 1 μg/mL, which corresponds to eightfold reduction (Table 1). EtBr-potentiation effects of quercetin and its conjugates (1)(2)(3)(4)(5)(6) were evaluated by the same method but only the 7-O-substituted quercetin conjugates (2-3, 5-6) potentiated the antimicrobial activity of EtBr against the wild-type S. aureus with MECs of 8~32 μg/mL ( Table 1). The 3-O-substituted conjugates (1 and 4), on the other hand, did not exert any effect on the antimicrobial activity of EtBr, which is reminiscent of their lack of inhibitory activity against mammalian Pgp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the presence of reserpine (MEC, 4 μg/mL), the MIC of EtBr was reduced to 1 μg/mL, which corresponds to eightfold reduction (Table 1). EtBr-potentiation effects of quercetin and its conjugates (1)(2)(3)(4)(5)(6) were evaluated by the same method but only the 7-O-substituted quercetin conjugates (2-3, 5-6) potentiated the antimicrobial activity of EtBr against the wild-type S. aureus with MECs of 8~32 μg/mL ( Table 1). The 3-O-substituted conjugates (1 and 4), on the other hand, did not exert any effect on the antimicrobial activity of EtBr, which is reminiscent of their lack of inhibitory activity against mammalian Pgp.…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type S. aureus strain was a kind gift from Professor YongSup Yi, Hoseo University. A modified broth dilution method was used to determine the minimum inhibitory concentrations (MICs) of antibiotics (reserpine, EtBr, tetracycline, ciprofloxacin, gentamycin, and erythromycin) against S. aureus strain in Muller-Hinton broth in the absence and presence of the quercetin conjugates (1)(2)(3)(4)(5)(6). Three serial dilutions of the quercetin conjugates (50, 25, and 10 μg/ mL) were tested in combination with 10 serial dilutions of antibiotics (512-1 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…P‐glycoprotein (Pgp)‐mediated anticancer drug efflux is the most well‐characterized cellular mechanism of cancer MDR, and quercetin is known to have MDR‐reversing activity via inhibition of Pgp . Previously, we have shown that the MDR‐reversing activity of quercetin could be significantly enhanced via conjugation with an amino acid . Thus, a quercetin–glutamic acid conjugate (7‐ O ‐Glu‐Q, Figure ) sensitized MDR cells to various anticancer drugs with EC 50 values of 0.8–0.9 μM through direct inhibition of drug efflux by Pgp .…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have shown that the MDR‐reversing activity of quercetin could be significantly enhanced via conjugation with an amino acid . Thus, a quercetin–glutamic acid conjugate (7‐ O ‐Glu‐Q, Figure ) sensitized MDR cells to various anticancer drugs with EC 50 values of 0.8–0.9 μM through direct inhibition of drug efflux by Pgp . Interestingly, even though 7‐ O ‐Glu‐Q was designed to afford free quercetin after intracellular cleavage of the carbamate linkage between quercetin and glutamic acid, Pgp ATPase assay indicated that the intact 7‐ O ‐Glu‐Q binds to Pgp more strongly than quercetin .…”
Section: Methodsmentioning
confidence: 99%
“…[56,57] Clinical trial data of third-generation inhibitors (ariquidar, zosuquidar and elacridar) are awaited for possible clinical application of this treatment approach. [58] Other naturally occurring compounds such as curcumin, [59] quercetin, [60,61] and kaempferol are being studied and modified for use in brain cancer therapy to overcome the problem of multidrug resistance (MDR). [62] Barthomeuf et al [22] studied the use of curcuminoid compounds to enhance the clinical efficacy of docetaxel for the treatment of cancers including GBM.…”
Section: Receptor Mediated Transcytosismentioning
confidence: 99%